PROSPECTS AND RESULTS OF STUDYING THE COLLECTION OF CHICKPEA FROM VIR AT OMSK STATE AGRARIAN UNIVERSITY - S. P. Kuzmina; N. G. Kazydub; E. A. Chernenko (Труды по прикладной ботанике, генетике и селекции)
In 2012-1016, 23 chickpea accessions from VIR and 23 accessions from the collection of chickpea somaclones of the Siberian Research Institute of Forages were studied at Omsk State Agrarian University. The research performed in the southern forest-steppe of West Siberia resulted in identifying chickpea accessions with a shorter growing season, high plant productivity, good processability, and high symbiotic activity. The possibility of using cluster analysis for comprehensive assessment of source material for chickpea breeding was demonstrated. The nature of inheritance of agronomic traits in F1 chickpea hybrids was revealed, and recommendations for selection were formulated. A correlation was established between the major characters.